The effectiveness of the Beneish model in the detection of accounting violations – the example of companies sanctioned by the Polish Financial Supervision Authority - Comporek, Michał (Skuteczność modelu Beneisha w wykrywaniu manipulacji księgowych na przykładzie spółek ukaranych przez Komisję Nadzoru Finansowego, 2020)
The main purpose of the paper is to assess the effectiveness of the eight-factor Beneish model in detecting manipulations in the financial statements of public companies listed on the Warsaw Stock Exchange. The research sample consists of 27 enterprises that were sanctioned at least once by the PFSA for irregularities in compliance with the IAS/ IFRS principles in the period 2006-2018. Empirical analysis proved that in the selected group of enterprises, the original version of the Beneish model is characterized by a relatively low degree of usefulness, thus it should be considered as an average tool supporting the work of auditors, statutory auditors and stock exchange investors, and at the same time a starting point for the further search for instruments to detect accounting violations, developed and adapted to conditions of the Polish capital market
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 10, s. 18-30